O-031 Role of resistivity index analysis in the prediction of hemodynamically significant venous sinus stenosis in patients with idiopathic intracranial hypertension. (22nd July 2019) - Mohammaden, M; Rizwan Husain, M; Brunozzi, D; Atwal, G; Charbel, F; Alaraj, A
Abstract : Background: The resistivity index (RI) in cerebral venous sinus stenosis (VSS) has not been studied in patients with idiopathic intracranial hypertension (IIH). Objective: To evaluate the role of resistivity index (RI) measured by quantitative MRV (QMRV) as a non-invasive tool in the diagnosis of venous hypertension associated with VSS in idiopathic intracranial hypertension (IIH). Methods: Retrospective evaluation of 13 consecutive IIH patients who underwent venous sinus stenting at our institution between 2013–2018 was reviewed. Patients' demographics, clinical presentation, cerebral mean venous sinus pressure (MVP) and RI both pre and post-stenting were recorded. The baseline RI was also compared to a control group. Results: Among 13 patients of IIH, 11 had unilateral VSS in dominant sinus, while 2 had bilateral VSS. RI was significantly higher in IIH patients compared to the control group in the superior sagittal (SSS) and transverse sinuses (TS) (0.21 vs 0.11, p = 0.01 and 0.22 vs 0.13, p = 0.03, respectively). The MVP (in mmHg) decreased significantly after venous sinus stenting in the SSS (41.9 to 22.5, p<0.001) and TS (39.4 to 19.5, p<0.001) which was also associated with a significant reduction of the RI (0.22 vs. 0.17, p<0.01 in SSS and 0.23 vs. 0.17, p = 0.03 in TS) post-stenting. Conclusion: RI calculated using QMRV can serve as a non-invasive tool to aid in the diagnosis of hemodynamically significant VSS. The study had a small sample size, and larger multicenter studies would be required to validate the results further. Disclosures: M. Mohammaden: None. M. Rizwan Husain: None. D. Brunozzi: None. G. Atwal: None. F. Charbel: None. A. Alaraj: 1; C; NIH. 2; C; Cerenovus.